Morphometric study of trachea in adult cadavers - Bhandari, R; Ranjit , N; Shrestha , R; Shrestha , A; Adhikari , B; Shrestha , RN (Journal of Institute of Medicine Nepal, 2018)
Introduction: Knowledge of tracheal morphometry is essential for carrying out interventional procedures of the airway like endotracheal intubation, tracheostomy and tracheal stenting. It has been described that the length of human trachea ranges from 10 to 11 cm and the internal tracheal diameter in transverse axis is about 12 mm in adults. The main objective of this study is to evaluate the tracheal length and its internal and external diameters from adult Nepalese cadavers.Methods: A total number of 182 cadavers, 132 male and 50 female, with Nepalese nationality were studied. The study subjects were 18 years or above. Tracheal length, internal and external tracheal diameters in anteroposterior and transverse axes were measured after photographic record of the sample.Result: The mean tracheal length was 82.87 ± 8.3 mm in male and 77.59 ± 9.3 mm in female. The TEDAP were 18.95 ± 2.0 mm and 15.83 ± 2.2 mm in male and female respectively. The TEDTR were 23.73 ± 3.5 mm and 20.70 ± 3.0 mm in males and females respectively. The TIDAP in males was 9.34 ± 2.2 mm and in females was 6.88 ± 1.7 mm. The TIDTR was 13.24 ± 2.9 mm in males and 10.51 ± 2.9 mm in females.Conclusion: The tracheal dimensions of our study showed marked dissimilarity with those of the studies conducted in western population.